Dialect Differences in the Consciousness of the Inhabitants of the Russian North (With Reference to Oppositional Contexts) - Bondarenko, E. D. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2017)
This article considers cases of metalinguistic reflection of the Northern Russian folk tradition bearers regarding interdialectal differences presented in the form of opposed contexts — statements in which linguistic features of the bearers of two or more language varieties are deliberately contrasted. The main data for the study are presented by metalinguistic text formations collected during the fieldwork of the Toponymic Expedition of Ural Federal University between 2005 and 2016. The article aims to highlight the peculiarities of the naïve linguistic consciousness concerning dialect distinctions on different language levels (phonetics, prosody, vocabulary), as well as to analyse metalinguistic statements about the sociolingustic and linguogeographic parameters underlying the opposition of different dialects. As a result of opposed contexts analysis, the author determines a number of phonetic features of the Russian Northern dialects. These features serve as a basis for the division “one’s own dialect” — “another dialect” in naïve linguistic consciousness: progressive assimilation (palatalisation) of velar consonants, yjr pronunciation of [ў] instead of [l], simplification of the combination [cht’], pronunciation [ch] as [ts] and [o] as [a], etc. The author also singles out some features regarded as irrelevant by naïve dialectologists and describes peculiarities of the “naïve” perception of dialect vocabulary features (inter-dialectal synonymy and homonymy). Additionally, she describes a number of the most frequent words, indicating dialectal differences (clothes, pastry, tools, mushrooms, typical addresses, and personal names, etc.). The article refers to the main sociolinguistic oppositions, which are relevant for dialect speakers (“Russian” — “non-Russian”, “urban” — “rural”). The article makes an attempt to retrace relative “naïve” isoglosses. The author shows several boundaries and areas marked by naive “dialectologists”.